The management of Sjögren's syndrome: British Society for Rheumatology guideline scope. (2nd February 2021) - Price, Elizabeth; Allen, Alexander; Rauz, Saaeha; Tappuni, Anwar; Sutcliffe, Nurhan; Bombardieri, Michele; Carty, Sara; Ciurtin, Coziana; Crampton, Bridget; Duncalfe, Lisa; Fisher, Benjamin; Glennon, Peter; et al.
Abstract: The guideline will be developed using the methods and processes outlined in Creating Clinical Guidelines: Our Protocol [1 ]. This development process to produce guidance, advice and recommendations for practice has National Institute for Health and Care Excellence (NICE) accreditation.